Optimal tuned mass-damper-inerter (TMDI) design in wind-excited tall buildings for occupants' comfort serviceability performance and energy harvesting. (1st February 2020) - Petrini, Francesco; Giaralis, Agathoklis; Wang, Zixiao
Highlights: Optimal tuned mass damper inerter (TMDI) design for occupants' comfort in wind excited tall buildings subject to wind is addressed. Trading of secondary mass to inertance is quantified through performance-based design charts achieving lightweight TMDIs for target peak floor acceleration performance. Improved TMDI robustness to host structure properties and to reference wind velocity is achieved by TMDI topologies with inerters spanning more floors and/or by increased inertance. Increased available energy for harvesting in wind excited tall buildings is achieved by incorporating electromagnetic motors in TMDIs with varying damping property. Concurrently reduced floor acceleration and increased available energy for harvesting is accomplished by TMDI topologies with inerters spanning more floors. Abstract: The tuned mass-damper-inerter (TMDI) couples the classical tuned mass-damper (TMD) with an inerter device which develops a resisting force proportional to the relative acceleration of its ends by the "inertance" constant. Previous works demonstrated that the TMDI leads to efficient broadband vibration control for a range of different structures under different dynamic excitations. This paper proposes a novel optimal TMDI design formulation to address occupants' comfort in wind-excited slender tall buildings susceptible to vortex shedding (VS) effects and to explore optimal TMDI's potential for transforming part of the wind-induced kinetic energy to usable electricity in tall buildings. Attention is focused on investigating benefits of TMDIs with different inertial properties (i.e., secondary mass/weight and inertance) configured in different topologies defined by the number of floors spanned by the inerter device to connect the secondary mass to the building structure. Optimally designed TMDIs for a wide range of inertial properties and three different topologies are obtained through numerical solution of the underlying optimization problem for a benchmark 305.9 m tall building with more than 6 height-to-width ratio subjected to experimentally calibrated spatially-correlated across-wind force field accounting for VS effects. Fixed performance design graphs on the TMDI inertial (mass-inertance) plane are furnished demonstrating that any fixed structural performance level in terms of occupants' comfort (i.e., peak top floor acceleration) can be achieved through lightweight TMDIs as long as sufficient inertance is provided. Further, TMDI robustness to host structure properties and to reference wind velocity is shown to increase by increasing inertance or by spanning more floors in connecting the secondary mass with the host structure by the inerter. Lastly, it is found that increased available energy for harvesting in wind excited tall buildings is achieved by incorporating electromagnetic motors in TMDIs with varying damping property, while concurrent reduced floor acceleration and increased available energy for harvesting is accomplished by TMDI topologies with inerters spanning more floors.